Model of Food Security Software for Evaluation the Food Security Development: Case Study in Bandung City - Roni Kastaman; Insy Alimatun Hasanah; Totok Pujianto; Efri Mardawati (Universitas Padjadjaran, 2017)
In order to evaluation the food security development in Bandung, researcher has been conducted in the form of software design to measure the performance of food security development from the aspect of food availability, food accessibility and the utilization and quality of food. The software is created in Microsoft Excel base as an analytics tool. The data used as the material of analysis was taken from the report of the institutions related to the food security development. Data here, is a source for scoring and weghting of the 3 food security dimensions which is filled in the software. List of contents for the analysis of food availability, food access and utilization and quality of food aspect are consist of 27 criteria, 12 criteria and 12 criteria respectively. The evaluation is done based on the calculation of the total value of weight multiplication with the score of each criteria, where the maximum total value is 5000 and minimum 1000. Justification of performance condition of food security performance described in the software is based on 5 categories class, that is from 1000 to 1800 total value performance for “unsafe conditions”, then 1800 to 2600 for “unsafe conditions”, 2600 to 3400 for “fairly safe conditions”, 3400 to 4200 for “safe conditions” and 4200 to 5000 for “very safe conditions”. The result of evaluation by using data in Bandung City of year 2012 and year 2015 indicate that condition of Bandung food security in terms of availability is “fairly safe”, food access is “safe” and the utilization and quality of food is in “fairly safe” condition.